The association between perceived stress with sleep quality, insomnia, anxiety and depression in kidney transplant recipients during Covid-19 pandemic - VELİOĞLU, ARZU; TUĞLULAR, ZÜBEYDE SERHAN (PUBLIC LIBRARY SCIENCE, 2021)
Background The psychological distress and sleep problems caused by current Covid-19 outbreak is not well known in kidney transplant recipients. In this study, we aimed to investigate the association between perceived stress with sleep quality, insomnia, anxiety, depression and kidney function in kidney transplant recipients during the Covid-19 pandemic. Material and methods A hundred-six kidney transplant recipients were enrolled. Questionnaire of Socio-demographics, Perceived Stress Scale (PSS), Pittsburgh Sleep Quality Index (PSQI), Insomnia Severity Index (ISO and Hospital Anxiety Depression Scale (HADS) are performed. The laboratory data is recorded. The perceived stress related to Covid-19 pandemic and its associations were investigated. Results The mean age of patients was 44.2 +/- 13.3 years, and 65 of the patients (61.3%) were men. Forty-nine (46.2%) of the patients had high-perceived stress; 51 (48.1%) of the patients had poor sleep quality, 40 (37.7%) of the patients had insomnia, 25 (23.6%) of the patients had anxiety and 47 (44.3%) of the patients had depression. The patients having a history of Covid-19 infection in own or closed relatives (9.09 +/- 4.17 vs 6.49 +/- 4.16, p:0.014) and the patients who have a rejection episode any of time (8.24 +/- 5.16 vs 6.37 +/- 3.57, p:0.033) have had significantly higher anxiety scores, when they compared to others. The high PSS were positively correlated with PSQI, ISI, HAD-A and HAD-D. Regression analyses revealed that high-perceived stress is an independent predictor of anxiety and depression. There was not significant difference between kidney function with PSS, PSQI, ISI, HAD-A and HAD-D. Conclusions High PSS is positively correlated with poor sleep quality and insomnia and also an independent predictor of anxiety and depression in kidney transplant recipients during the outbreak of Covid-19. As the pandemic is still spreading worldwide quickly early identification and intervention of sleep disturbances and psychiatric disorders are essential to protect graft function with high compliance to treatment in transplantation patients.
Keywords: RENAL-TRANSPLANTATION; SEVERITY INDEX; IMMUNOSUPPRESSANTS; VALIDATION; DISORDERS; IMPACT